VIDA ÚTIL Y BENEFICIOS DE LOS NUTRACÉUTICOS COMO ALTERNATIVAS AL ÓXIDO DE ZINC - Torralbo Martín, Andrea; Serrano Jara, Daniel; Cubero Pablo, María José; Jordán Bueso, María José; Martínez Conesa, Cristina; Rivera Gomis, Jorge (Anales de veterinaria de Murcia, 2024)
Weaning is one of the most critical stages in pig production, often giving rise to diarrhoea. ZnO has been widely used, until its ban in Europe in 2022. The bioactive compounds of oregano and purple garlic are the subject of study in this research for their medicinal properties and could be alternatives to ZnO and antibiotics. Seven dietary treatments were compared: a negative control group (basal diet), a positive control group with zinc oxide (2500 mg/kg of food), two groups with oregano essential oil at 0.4% and 1.2%. respectively, two groups with ground purple garlic at 0.4% and 2% respectively, and one group with oregano essential oil at 1.2% combined with ground purple garlic at 2%. The treatments were carried out after weaning at 21 days, for 2 weeks in the pre-starter and for 5 weeks in the starter. At the end of 10 weeks, the piglets were weighed, and necropsy was performed to take samples of the jejunum and ileum and evaluate their morphometry. We have studied the impact of the degradation of nutraceuticals during their storage in silos, as well as its impact on the morphometry of the jejunum and ileum and its influence on productive performance such as average daily gain and conversion rate. When evaluating the degradation of bioactive compounds in feed, stored for 5 weeks, it was concluded that there was a 30% loss in both oregano and purple garlic. However, there were no significant differences in productive performance and intestinal morphometry between the treatment with zinc oxide and the combination of 2% ground purple garlic and 1.2% oregano essential oil. In conclusion, these doses are a good alternative as growth promoters and for the prevention of post-weaning diarrhoea. El destete es una de las etapas más críticas en la producción porcina, con frecuentes diarreas. Se ha utilizado ampliamente el óxido de Zinc (ZnO), hasta su prohibición en Europa en 2022. Los compuestos bioactivos del orégano y el ajo morado fueron investigados por sus propiedades medicinales, y podrían ser alternativas al ZnO y a los antibióticos. Se compararon siete tratamientos dietéticos: un grupo control negativo (dieta basal), un grupo control positivo con ZnO (2500 mg/kg de alimento), dos grupos con aceite esencial de orégano al 0.4% y al 1.2% respectivamente, dos grupos con moltura de ajo morado al 0.4% y al 2% respectivamente, y un grupo con aceite esencial de orégano al 1.2% combinado con moltura de ajo morado al 2%. Los tratamientos se realizaron tras el destete a los 21 días, durante 2 semanas en el pre- estárter y durante 5 semanas en el estárter. Al finalizar las 10 semanas, los lechones se pesaron y se realizó la necropsia para tomar muestras de yeyuno e íleon y evaluar su morfometría. Hemos estudiado el impacto de la degradación de los nutracéuticos durante su almacenamiento en los silos, así como su repercusión sobre la morfometría del yeyuno e íleon y su influencia en la ganancia media diaria y el índice de conversión. Al evaluar la degradación de los compuestos bioactivos en los piensos, almacenados durante 5 semanas, se identificó una pérdida del 30% tanto en el orégano como en el ajo morado. No obstante, no hubo diferencias significativas en el rendimiento productivo y la morfometría intestinal entre el tratamiento con ZnO y el combinado de moltura de ajo morado al 2% y el aceite esencial de orégano al 1.2%. En conclusión, estas dosis son una buena alternativa como promotores del crecimiento y para la prevención de la diarrea post- destete.